Perancangan Storyboard Konten Animasi 3 Dimensi Untuk Edukasi Anak Usia Sekolah Dasar Tentang Mitigasi Penyebaran COVID-19 - Zulfan Zulfan; Nailis Sa’adah; Said Mustafa; Munawir Munawir; Erdiwansyah Erdiwansyah; Susmanto Susmanto; Taufik Hidayat (Fakultas Teknik, 2022)
The spread of the COVID-19 virus has been widespread all over the world since its discovery in 2019. However, the spread of this virus can be prevented by means of health protocols conforming to World Health Organization standards. The Indonesian government continues to educate the public, especially school-aged children, to understand how to implement the health protocol. On the basis of the foregoing, it is necessary to carry out research on the creation of an interactive media based on multimedia content that can be used to educate on COVID-19 prevention, specifically for elementary school children. The research begins with problem analysis, storyboard writing, creating 3D animation characters, and merging all content into a complete 3D animation video. The results of this study are 3D animated multimedia content which presents 3D animated scenes on the application of health protocols such as hand washing with soap, wear masks and keep distance.